1987
DOI: 10.1007/bf00272440
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Y-specific DNA sequences in human 46,XX true hermaphrodites and in 45,X mixed gonadal dysgenesis

Abstract: A search for Y-specific DNA sequences has been performed in a sample of seven 46,XX true hermaphrodites and one 45,X mixed gonadal dysgenesis case and compared with a sample of 11 XX males. Using six Y-specific DNA probes no hybridization signal was obtained in the hermaphrodite group; in contrast, all XX males gave a positive signal with at least one probe. This difference is statistically highly significant. We conclude that the aetiology of true hermaphroditism is different from that of the XX male syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…However, several publications have recently evidenced that this condition is not so simple [9][10][11][12], and people should avoid oversimplification.…”
Section: Commentsmentioning
confidence: 99%
“…However, several publications have recently evidenced that this condition is not so simple [9][10][11][12], and people should avoid oversimplification.…”
Section: Commentsmentioning
confidence: 99%
“…It has been suggested that this latter category includes a subgroup of either sporadic or familial cases who exhibit a particular phenotype with ambiguous external genitalia. One possible explanation is that maleness in Y(-) XX males and in 46,XX true hermaphrodites is caused by an autosom al gene with somewhat different phenotypic expression (Abbas et al HGM9;de la Chapelle, 1987;HGM9;Waibel et al 1987). As a consequence of the terminal X-Y interchange, most Y( + ) XX males can be classified according to the amount of Y DNA they have inherited.…”
Section: Males and Xy Femalesmentioning
confidence: 99%
“…Several probes like DYS13 (GMGY3; Affara et al 1986b), DYS104 (27a; Pritchard et al 1987a) and DXYS49 (Fr80-II; Waibel et al 1987) appear to detect a high percentage of XX males and may therefore map in the close vicinity of TDF.…”
Section: Males and Xy Femalesmentioning
confidence: 99%
“…The Yp probe Fr35-II (Waibel et al, 1987) was used along with the 16q terminal probes H36 (H. Dauwerse, personal communication; Dauwerse et al, 1989), BBC1 (Cleton-Jansen et al, 1994), and CRI0.89 (Keith et al, 1987). All probes were labeled with biotin by nick translation.…”
Section: Cytogenetic Investigation On Lymphocyte Metaphasesmentioning
confidence: 99%